2017
DOI: 10.1021/acsami.7b06839
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL8/AuNPs-rGO/ITO as an Immunosensing Platform for Noninvasive Electrochemical Detection of Oral Cancer

Abstract: An efficient electrochemical transducer matrix for biosensing devices requires specific characteristics, such as fast electron transfer, stability, high surface area, biocompatibility, and presence of specific functional groups, to facilitate biomolecule attachment. We demonstrate the fabrication of an electrochemical immunosensor based on a highly stable gold nanoparticles-reduced graphene oxide (AuNPs-rGO) composite material as a transducer matrix for label-free and noninvasive detection of salivary oral can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(91 citation statements)
references
References 60 publications
3
88
0
Order By: Relevance
“…3a. C 1 s core levels have been fitted using five near Gaussian components which correspond to C=C/C-C, C-OH, C-O, C=O, and -COOH [24]. Attachment of PtCo(1:9) to rGO results in further reduction as C-O component of C 1 s core level in PtCo(1:9)/rGO is significantly reduced compared to rGO sample.…”
Section: Resultsmentioning
confidence: 99%
“…3a. C 1 s core levels have been fitted using five near Gaussian components which correspond to C=C/C-C, C-OH, C-O, C=O, and -COOH [24]. Attachment of PtCo(1:9) to rGO results in further reduction as C-O component of C 1 s core level in PtCo(1:9)/rGO is significantly reduced compared to rGO sample.…”
Section: Resultsmentioning
confidence: 99%
“…The linear fitting curve showed that the peak current had a linear relationship with the square roots of the scanning rates having regression coefficient (R 2 ) of 0.9915 for Ipa and 0.9923 for Ipc respectively, which indicated the redox process to be a diffusion controlled electrochemical process. 32,33 At the same time, the blank CV curve of UOx/Fc/Cu 2 O/GCE in 0.1 M KCl were detected. The results (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Since, electrocataysis phenomena are surface charge dependent, the concentration of ionic species at electrode surface plays an important role. Therefore, in order to assess the concentration of ionic species ( I * ) using Brown‐Anson model (Equation 5) is used . truenormalIp=n2F2I*AV4RT …”
Section: Resultsmentioning
confidence: 99%